The Impact of 5G Network Technology Transformation to Replace 4G Using the Sem Amos Method - Afriyanto, Dody; Destya, Senie (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
The development of the telecommunication world has occurred very rapidly and has been brought from the first generation, namely 1G to 4G, which has developed as a future network medium in several countries, successfully implemented in transactions. This research discusses the potential of 5G technology as a substitute for the previous technology, namely 4G. How can this technology be applied in Indonesia; which areas are suitable for implementing 5G technology? Data analysis for this study has been adapted to the research model and the variables studied. The causality model is used in this study, and the AMOS program's SEM (Structural Equation Modeling) analysis method is used to assess the research assumptions. The existence of the 5G network has brought Indonesia to the threshold of development that opens the door to a world full of opportunities, 5G technology is expected to have a positive impact on the development of digital skills and entrepreneurship, which will have a better impact.